Aqueous molybdate provides effective corrosion inhibition of WE43 magnesium alloy in sodium chloride solutions. (September 2021) - Kharitonov, Dmitry S.; Zimowska, Małgorzata; Ryl, Jacek; Zieliński, Artur; Osipenko, Maria A.; Adamiec, Janusz; Wrzesińska, Angelika; Claesson, Per M.; Kurilo, Irina I.
Highlights: Corrosion properties of WE43 Mg alloy in 0.05 M NaCl solution have been examined. Na2 MoO4 inhibitor provides reliable inhibition in concentrations at and above 100 mM. XPS and confocal Raman measurements revealed the chemical state of molybdenum compounds. Inhibition effect is provided by a surface film of mixed Mo(V)–Mo(VI) species. A two-step oxidation-reduction mechanism of corrosion inhibition has been proposed. Abstract: Corrosion and corrosion inhibition of WE43 magnesium alloy were investigated in NaCl solutions containing different amounts of sodium molybdate. Electrochemical, microscopic, and spectroscopic experiments were utilized to examine the mechanism of corrosion inhibition by molybdates. Electrochemical data showed that Na2 MoO4 inhibitor provides reliable inhibition at concentrations at and above 100 mM. Raman and XPS spectroscopy demonstrated that the formed surface layer consists of mixed Mo(V, IV) species. This layer provided inhibition with an efficiency of 91–99 % after 24 h of exposure. A two-step oxidation-reduction mechanism of corrosion inhibition of the WE43 alloy by aqueous molybdates was proposed.